Accessing Capital Resources: Investigating the Effects of Teacher Human and Social Capital on Student Achievement. Issue 7 (July 2014) - Daly, Alan J.; Moolenaar, Nienke M.; Der-Martirosian, Claudia; Liou, Yi-Hwa
Background: A growing empirical base suggests that there is a positive relationship between teacher social interaction and student achievement. However, much of this research is based on standardized summative assessments, which, while important, may have limited applicability to timely instructional decision making. As such, in this work, we examine the relationship between teacher social interaction and interim benchmark formative assessments, which have been argued to play a more useful role in instructional decision making. Purpose: In this study we used a human and social capital framework to explore the relationship between teacher social interaction and student achievement on an interim benchmark formative assessment. We hypothesized that teacher social capital would be positively related with student achievement as measured by an interim assessment, even after controlling for student and teacher demographics as well as proxies for teacher human capital. Population: A sample of 63 teachers from five elementary schools in a midsize U.S. district completed a demographic and social network survey, from which we generated our human and social capital measures. For student-level data, we collected current and prior student achievement from 1, 196 third to fifth grade students on an English Language Arts Interim Benchmark Assessment. Research Design: We used survey data to conduct social network analysis and hierarchical linear modeling to explore the multilevel relationship between human and social capital and student achievement. Results: Results indicated that even when controlling for student demographics and prior achievement, teachers' human and social capital had a significant effect on student achievement as measured by interim assessments. More specifically our results indicated that more teaching experience in the current school was associated with better student performance on the interim assessment. In addition, the act of reaching out to other teachers to share knowledge regarding reading comprehension was associated with higher student scores on the interim assessment even when controlling for demographics and past academic performance. Conclusions: This study offers a unique insight into the role of accessing capital resources and student achievement in strengthening schools under increased pressure to improve. Our work adds to the growing empirical base that suggests that teacher social interaction has a relationship with student achievement. To encourage social interaction, creating formal policies and structures for teachers to develop social ties with one another related to content may be a useful strategy in supporting student outcomes.